Momordica Charantia L-An Ethnobotanical Drug - POONAM SETHI, (International Journal of Pharma and Bio Sciences, 2012)
Leaves of Momordica charantia L or bitter melon or bitter gourd (Cucurbitaceae) an active ingredient of many ayurvedic preparations mainly against diabetes was studied for its pharmacognisical characters. The trace elements and the mineral content of the leaves were also evaluated. Ethanolic extracts of the leaves reported in vitro antibacterial activities against gram negative bacteria such as Salmonella typhi, Pseudomonas fluorescens, Pseudomonas aeruginosa and Escherichia coli. The pathogens were tested by disc diffusion assay method and a minimum inhibitory concentration was evaluated. An attempt was made to compare the activity of the extract with a standard antibiotic ciprofloxin. The pharmacognisical and the phytochemical constituents help in proving the authencity of the drug. In addition it proves the efficacy of the plant as an antibacterial agent.